THE ROLE AND IMPORTANCE OF HOPE IN THE EDUCATION OF CHILDREN OF PRIMARY EDUCATIONAL AGE - Alisher Narmanov (Web of Journals Publishing, 2024)
The article discusses the role and importance of hopi in the education of children of primary education age.
Keywords: primary education, pedagogy, young children, education, hopi, importance.